Empowerment in agricultural value chains: Mixed methods evidence from the Philippines - Malapit, Hazel J.; Ragasa, Catherine; Martinez, Elena M.; Rubin, Deborah; Seymour, Greg; Quisumbing, Agnes R. (International Food Policy Research Institute, 2019)
Women’s participation and empowerment in value chains are goals that concern many development organizations, but there has been limited systematic, rigorous research to track these goals between and within value chains (VCs). We use the survey-based project-level Women’s Empowerment in Agriculture Index (pro-WEAI) to measure women’s and men’s empowerment in the abaca, coconut, seaweed, and swine VCs in the Philippines. Results show that most women and men in all four VCs are disempowered, but unlike in many other countries, Filipino women in this sample are generally as empowered as men. Pro-WEAI results suggest that respect within the household and attitudes about gender-based violence (GBV) are the largest sources of disempowerment for both women and men, followed by control over use of income and autonomy in income-related decisions. Excessive workload and lack of group membership are other important sources of disempowerment, with some variation across VCs and nodes along VCs. Across all four VCs, access to community programs is associated with higher women’s empowerment, and access to extension services and education are associated with higher men’s empowerment. Our results show that, despite the egalitarian gender norms in the Philippines, persistent gender stereotypes influence men’s and women’s empowerment and VC participation.